Peramalan Inflasi Kota Pontianak dengan Metode Seasonal Autoregressive Integrated Moving Average - Aulia, Alwa; Huda, Nur'ainul Miftahul; Rofatunnisa, Sifa (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
One measure of regional economic stability that is always interesting to discuss is inflation, as it has a major impact on economic growth, external balance, competitiveness, interest rates, and even income distribution. Inflation is a term that refers to a consistent rise in the prices of goods and services over a period of time. This rise in prices can lead to a decrease in the purchasing power of money. To solve this problem, it is necessary to make predictions to forecast the value of inflation in the future. This research uses the Seasonal Autoregressive Moving Average method to forecast Pontianak City inflation from January 2025 to December 2025. The data used in this research comes from BPS Pontianak City. The best model is determined from the accuracy test with MAPE value. Based on the results of the analysis conducted, the ???????????????????????? (6,0,4)(2,1,1)6 model is the best model for forecasting inflation in Pontianak City with a MAPE value of 2.02%.